Meta-analysis review of the literature on urban housing production from an Actor-network theory perspective - Baghal, Aysegul; Cinar Citak, Candan (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2024)
Urban areas are dynamic and complex systems. In the built environment, reshaping and reconstructing urban spaces for a sustainable future raises not only physical and spatial challenges but also issues around stakeholder relations. Urban area production, consumption, use, and management processes involve complex interactions between heterogeneous assets. In recent years, understanding inter-stakeholder networks has been crucial for urban growth and transformation decision-making mechanisms. Urban transformation is a complex and multifaceted process that requires comprehensive and integrated methods involving stakeholders and addressing economic, social, and environmental aspects. Scientific approaches are necessary for dealing with cities'complex, dynamic growth due to social and physical factors. This article evaluates actor-network theory (ANT), one of many approaches to resolving social relations, as a conceptual framework for its ability to unravel the entire network of relationships between actors, objects, and things involved in housing production processes in urban studies. The primary objective of the study is to construct a framework for decision-making models by analyzing housing production systems, both locally and globally, from the perspective of actor-network theory. This is achieved by analyzing stakeholder network relationships through meta-analyses of literature and ANT-based case studies, considering political, sociological, and historical differences. For developing decision-making models, articles reviewed in the meta- analysis framework are classified into four categories: (1) policies and strategies; (2) stakeholders and actors; (3) approaches and tools; and (4) potentials and risks. The study findings are expected to contribute to the development of decision-making models for urban transformation practices.
Keywords: Actor-network theory (ANT); actors; meta-analysis; urban housing production; stakeholders; CHALLENGES; KNOWLEDGE; QUALITY; Architecture